Solusi Numerik Model Verhulst Pada Estimasi Hasil Panen Melalui Perkembangan Produksi Padi dan Beras dengan Metode Milne-Simpson - Arjuna, Dimas Bagus; Lubis, Riri Syafitri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The aim of this research is to develop a numerical solution using the Verhulst model to estimate paddy and rice production in North Sumatra. The Milne-Simpson method is used in this research to provide an efficient numerical approach in solving the model, with the aim of increasing the accuracy and effectiveness of estimating rice plant growth and rice production in the North Sumatra region through a systematic and computational approach. In this research, the Milne-Simpson method is used to estimate paddy and rice production results in the following year. The results show that the estimated rice production in North Sumatra Province is 2,086,590.76 tons in 2023 and 2,098,149 tons in 2024. Meanwhile, the estimated rice production in North Sumatra Province is 1,198,678.38 tons in 2023 and 1,207,384 tons in 2024. The results of this research also show that every year rice production increases by an average of 13,430 and rice production increases by an average of 8,254. Therefore, it can be seen that the estimated paddy and rice production in North Sumatra Province for 2023-2024 has increased.